Lembaga Dana Kerjasama Pembangunan Internasional Sebagai Alat Sentralisasi Soft Diplomacy Keuangan Indonesia (Administratio, 2021)
Indonesia has become an upper-middle-income country since 2020. It is also shifting Indonesia's role in foreign economic cooperation from a recipient country to a donor country. Indonesian foreign aid is not well managed so far because of a lack of coordination between the acting ministries and potentially inconsistent with Indonesia's foreign policy. This research uses qualitative methods through literature studies. The Indonesian Government has established Indonesian AID (LDKPI) to manage and centralize international economic cooperation and providing technical assistance to foreign governments/institutions. Professional and modern management of the institution in foreign aid will be aligned with the government's foreign diplomacy policy, reduce bureaucracy and business processes, also relieve the burden of the Indonesian state-budget.